Philosophy of technology the technological condition :an anthology - Scharff, Robert C.; Dusek, Val 1941- (Chichester, West Sussex Wiley Blackwell, 2014)
The new edition of this authoritative introduction to the philosophy of technology includes recent developments in the subject, while retaining the range and depth of its selection of seminal contributions and its much-admired editorial commentary. Remains the most comprehensive anthology on the philosophy of technology available. Includes editors' insightful section introductions and critical summaries for each selection. Revised and updated to reflect the latest developments in the field. Combines difficult to find seminal essays with a judicious selection.
Includes bibliographical references and index.
Keywords: Technology -- Philosophy